Leitura literária e educação do campo na formação inicial de professores - Pompermayer, Soraya Ferreira (2023)
This doctoral research investigates literary reading and field education in initial teacher training. The object of analysis was the Degree Course in Rural Education at the Federal University of Espírito Santo (LEdoC/UFES). The production, systematization, treatment and analysis of data was guided by the following problem: how does working with the literary text contribute to the initial formation of the reading teacher in rural education? This is a study carried out in the Research Group (CNPq) “Cultures, Partnerships and Rural Education” and in the Research Line “Teaching, Curriculum and Cultural Processes” of the Graduate Program in Education (PPGE) at UFES. The Network Research Working Group (GTPR) was created, from which two master's dissertations and the present thesis were produced. The research is anchored in the theoretical assumptions of Walter Benjamin (2012), specifically narration, and Mikhail Bakhtin (2003), dialogism. At the same time, it discusses issues of Rural Education, teacher training in Arroyo (2010), Molina (2014), Caldart (2015), Foerste (2009), among others. Dialogues on reading and reader formation and education in Freire (1998), Bakhtin (2003), Kramer (2000), Geraldi (1996) are deepened. This is a study based on qualitative approaches (ANDRE; LUDKE, 2012) focusing on dimensions of participatory research (BRANDÃO, 2001) with implications for action research (THIOLLENT, 1992; FRANCO, 2005), as well as Dialogical Analysis do Discurso – ADD (SOBRAL; GIACOMELI, 2016), (BRAIT, 2006) based on a collective construction in dialogue with the traditional peoples and communities of the course in question. It appears from the narratives of the research subjects that the Pedagogy of Alternation provides students in Community Time (TC) with the opportunity to have more time for reading, thus contributing to the formation of the reading teacher; a new reformulation of the curriculum is necessary and rethink the workload of some disciplines. The menus need to be revisited to encourage the formation of reading teachers. It is concluded that it is necessary to train the reading teacher in dialogue with the culture of peasant subjects, in order to enhance the collective production of a transforming praxis of literary reading in the initial training of teachers.